Oxygen enrichment of nutrient solution of substrate-grown vegetable crops under Mediterranean greenhouse conditions: oxygen content dynamics and crop response - Bonachela, S.; Acuña, R. A.; Magan, J. J.; Marfa, O. (Spanish Journal of Agricultural Research, 2010)
This work assessed the seasonal dynamics of the substrate oxygen content and the response to oxygen enrichment of nutrient solution (oxyfertigation) of autumn-winter sweet pepper and spring melon crops grown on rockwool slabs (2003/04 season) and perlite grow-bags (2004/05), compared to non-enriched crops. Dissolved Oxygen (DO) values in the nutrient solution were higher for all the oxygen enriched treatments (>20 mg L-1) than for the non-enriched ones ( 4 mg L-1), but no significant differences were found in the substrate solution. For pepper crops, DO values were highest at the onset and, especially, at the end of the cycle in winter, while the lowest DO values (3 to 4 mg L-1) occurred during September and October. For melon, DO values decreased progressively from the onset of the cycles to values ≤3 mg L-1 during the second half of the cycles. For pepper crops, there were no significant differences between oxygen treatments for fruit production, which could be attributed to the fact that DO values were >3 mg L-1 throughout each crop cycle. However, a significant 7% increase in total and marketable yield, associated with a higher fruit number, was observed for the oxygen enriched melon grown on rockwool slabs, whereas no significant differences were found for the melon grown on perlite grow-bags. In conclusion, the use of inexpensive systems of substrate oxygen enrichment should be restricted to rockwool substrates and to crop periods when a high oxygen demand coincides with low oxygen availability, such as the period from melon flowering phase.